Pemantauan Lingkungan Estuaria Perancak Berdasarkan Sebaran Makrobenthos [Environmental Monitoring Perancak Estuarine Based On Distribution Of Macrobenthos] - Abdul Manan; Taufik Indarmawan (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract One method to monitor the water quality is with macrobenthos studies. Motility of macrobenthos is very rare that more showed the characteristics of an environment. The aim of this study was to know the composition distribution in the region macrobenthos of Perancak estuarine for monitoring the condition of estuaries in the region. The method used is a descriptive method of data collection. Monitoring of macrobenthos distribution includes several stages such as stage of the survey and ground check, preparation tools and materials, taking physical and chemical parameters in the field, the separation and identification of samples and the last is the data analysis. The results of this monitoring showed characteristic macrobenthos of Perancak estuarine region consists of group annelids, crustaceans, gastropods and bivalves. Diversity index (H ') may be early prediction of the environmental quality of Perancak estuarine (bio-monitoring) showed there were distinct differences in contamination concentration at each station from severe to mild category.